A positive fluid balance does not deteriorate tissue metabolism during fluid resuscitation of sepsis - Koci, Jaromir; Oberreiter, Martin; Hyspler, Radek; Ticha, Alena; Valis, Martin; Lochman, Petr; Havel, Eduard; Ferko, Alexander (Neuro endocrinology letters, 2011)
OBJECTIVE: Hypovolemia has occurs frequently in sepsis. Due to pathologically increased permeability of the capillaries, the fluid leaks to the interstitium. An adequate fluid therapy is the corner stone to achieve circulatory stabilization and sufficient tissue perfusion; on the other hand, according to the data from the literature a tissue swelling is associated with a risk of deteriorated function of the tissues. The study aimed to examine the effect of a positive fluid balance on muscular metabolism. METHODS: The experimental study employed the model of sepsis in the domestical pig. Ten animals were randomly distributed into a control and a septic group. Sepsis was induced by intravenous administration of E. coli, followed by fluid resuscitation by crystaloids. Microdialysis samples were withdrawn at one-hour intervals for a period of 24 hours and values of lactate, pyruvate, glycerol, and glucose. RESULTS: Pearson's method revealed positive correlations between the lactate/pyruvate ratio and cumulative fluid balance in the septic group (R=0.292, p<0.001) and negative correlations in the control group (R=-0.279, p<0.05). In both groups, however, there was a gradual significant decrease in glycerol values. CONCLUSION: Fluid resuscitation results in positive fluid balance in both septic and control animals. This leads to circulatory stabilization of septic animals, but not a decrease in the anaerobic share of glycolysis. A positive fluid balance in control animals does not result in alteration of muscular aerobic glycolysis. Decreasing glycerol levels in both groups give evidence that a positive fluid balance does not exert a negative impact on cell metabolism.
Keywords: mikrodialýza; infekce vyvolané Escherichia coli; Escherichia coli Infections; Glycerol; kyselina pyrohroznová; Water-Electrolyte Balance; krystaloidní roztoky; glycerol; Sepsis; Plasma Substitutes; náhražky plazmy; Lactic Acid; sepse; hypovolemie; zvířata; Blood Glucose; Swine; resuscitace; Fluid Therapy; isotonické roztoky; Pyruvic Acid; Crystalloid Solutions; krevní glukóza; vodní a elektrolytová rovnováha; Resuscitation; Hypovolemia; Animals; Microdialysis; Isotonic Solutions; kyselina mléčná; prasata; tekutinová terapie